PENERAPAN MODEL EXPERIENTIAL LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERNALAR KRITIS PESERTA DIDIK - Sriningtias, Elok Alfi; Subekti, Hasan (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2023)
This research aims to describe (1) the implementation of learning using models Experiential Learning, (2) increasing critical thinking skills by applying models Experiential Learning, (3) the response of students after participating in learning with models Experiential Learning. The type of research used is type the one group pretest posttest. Data collection methods used in this study are observation, tests, and questionnaires. The instruments developed included learning implementation sheets, student worksheets, questions pretest posttest, and response questionnaires. The results of the study show that the results of the implementation of learning have a very good category at meetings 1 and 2. An increase in critical reasoning abilities is obtained from N-Gain of 0.65 with moderate improvement criteria. Responses of students after participating in learning with models Experiential Learning has an average percentage of 23.67% answered strongly agree, 72.67% answered agree, 3.67% answered disagree, and 0.33% answered strongly disagree.